Pengaruh Kompetensi, Perilaku Pimpinan, dan Kualitas Kerja Terhadap Efektivitas Kerja Pada Tim Kerja Program Tuberkulosis Puskesmas di Kabupaten Lingga - Herman, Hendri; Putra, Wirawan Trisna; Nurvianty, Nurvianty; Zurrahman, Zurrahman; Hajar , Siti (eScience Humanity Journal, 2024)
This research was conducted with the aim of understanding the influence of competence, leadership behavior, and work quality on work effectiveness within the tuberculosis program teams at community health centers in Lingga Regency. The total population in this study is 42 employees. The determination of the sample size uses the saturation sampling technique, which means that all members of the population are made part of the research sample. Thus, a total sample size of 42 respondents was obtained. The sampling technique is through probability sampling. Data collection was carried out by distributing questionnaires to the respondents. The collected data was processed using SPSS data processing software. The research findings indicate that, individually, competence has a significant effect on work effectiveness, leadership behavior has a significant effect on work effectiveness, and work quality has a significant effect on work effectiveness. Simultaneously, it is known that competence, leadership behavior, and work quality significantly influence work effectiveness. The adjusted R square value is 0.590 or 59%. This means that competence, leadership behavior, and work quality can explain the work effectiveness variable by 59%. Meanwhile, the remaining 41% is explained by other variables not included in this research model.